Long-Term Management Affects the Community Composition of Arable Soil Seedbanks. Issue 1 (17th November 2016) - Rotchés-Ribalta, Roser; Armengot, Laura; Mäder, Paul; Mayer, Jochen; Sans, Francesc Xavier
Abstract : The intensification of farming practices has reduced weed infestations, but it has also led to a reduction in weed diversity and changes in species composition. These effects are well described for aboveground flora; however, it is less clear how these effects might be expressed in the soil weed seedbank. We evaluated the effects of different long-term farm management strategies on the weed seedbank abundance, diversity, and community composition in the DOK (bioDynamic, bioOrganic, and Konventionell) field trial established in 1978 at Therwil, Switzerland. The trial compares biodynamic, organic, and conventional farming systems, which mainly differ in fertilization, weed control strategies, and pest control. The species richness and seed abundance of the weed seedbank were higher in the organic and biodynamic systems compared with the conventional ones. The different farming systems favored shifts in species assemblages, because specific management practices, such as herbicide application and type of fertilization, acted as filters that selected against certain species but promoted others that were more adapted.